2006
DOI: 10.1051/meca:2006056
|View full text |Cite
|
Sign up to set email alerts
|

Étude expérimentale des propriétés mécaniques et morphologiques dans un tube de gaz en HDPE-80

Abstract: L'objectif de cetteétude expérimentale est d'établir la distribution des propriétés mécaniques et morphologiquesà travers la paroi d'un tube de transport du gaz naturel en polyéthylène de haute densité (HDPE). L'approche proposée utilise un filament continu et uniforme, automatiquement usiné du tubeà faible vitesse de coupe età profondeur de passe optimale afin de réduire le flux de chaleur ainsi que les modifications structurales. Des courbes typiques (σ-ε), dans chaque couche, sont obtenues sur une machine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Typical properties of HDPE-100 and HDPE-80 polymers are provided in Table 1 [18]. The experimental tests following standard orthogonal table L9 (3) 3 were performed on two HDPE pipes 400 mm length each [20][21][22]. The HDPE-100 pipe had an outside diameter of 200 mm whereas the HDPE-80 had an outside diameter of 125 mm.…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical properties of HDPE-100 and HDPE-80 polymers are provided in Table 1 [18]. The experimental tests following standard orthogonal table L9 (3) 3 were performed on two HDPE pipes 400 mm length each [20][21][22]. The HDPE-100 pipe had an outside diameter of 200 mm whereas the HDPE-80 had an outside diameter of 125 mm.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Due to the nature of polymeric materials, polyethylene with excellent short-term mechanical strength can have poor long-term performance due to environmental stress cracking [14][15][16]. Manufacturing techniques do affect the mechanical behavior of HDPE in terms of elastic modulus, tensile strength and residual stresses [7,17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, each prepared specimen possess the particularity of having one machined side (turned or bored) and one extruded side (outer or inner pipe surface). 35,41 It is found that the recorded liquid sorption percent is different from one side to the other. Indeed it reached 2.2% in the inner layer and 1.9% in the outer layer.…”
Section: Dot 3 Oil Sorption By Hdpe Materialsmentioning
confidence: 98%
“…28 The mechanical parameters of Toluene-Methanol (TM) mixtures' effects on outer (OL) and inner (IL) pipe surface layers suggest that OL are rapidly degraded. 35 Usually, the analyzed structures imply important plasticization activities in the amorphous zones lowering the stress components. In addition, both LDPE and HDPE exposed to NG condensate exhibited the same type of plasticization.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…When considering temperature, the most secure case is given for 32°C which is a well-accepted upper bound by plastic pipe standards. (h) filaments, continuously machined in a given direction, and are used to study mechanical and structural heterogeneities across pipe wall imparted by manufacturing processes [4,[15][16][17]. Non-standard geometries are usually studied for specific applications and once technically approved by major pipe users; preliminary standards are prepared and put into standardized investigations to promote them as new standards.…”
Section: Introductionmentioning
confidence: 99%